2021
DOI: 10.1186/s12931-020-01601-y
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal reflux disease is a risk factor for sputum production in the general population: the Nagahama study

Abstract: Background Chronic sputum production in the general population is historically associated with clinical indices including male sex and smoking history. However, its relationship with gastroesophageal reflux disease (GERD), which may prove an underlying factor in sputum production, is unclear. We aimed to clarify factors associated with sputum production in the general population in cross-sectional and longitudinal manners. Methods In the Nagahama s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Furthermore, our study showed that the number of cough background disorders is associated with sputum production. These findings, alongside the findings of the previously mentioned Japanese study [ 13 ], suggest that the presence of sputum production in a patient with chronic cough should encourage a clinician to seek treatable cough background disorders especially carefully.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Furthermore, our study showed that the number of cough background disorders is associated with sputum production. These findings, alongside the findings of the previously mentioned Japanese study [ 13 ], suggest that the presence of sputum production in a patient with chronic cough should encourage a clinician to seek treatable cough background disorders especially carefully.…”
supporting
confidence: 55%
“…Sputum production was not statistically significantly associated with UACS or GORD in the present study. In a previous large Japanese study, both were statistically significantly associated with sputum production [ 13 ]. Different populations may explain this discrepancy.…”
mentioning
confidence: 99%
“…Many studies examining the relationship between these conditions fail to adequately discriminate between LPR and GORD (Lechien et al, 2023). One study demonstrated a positive relationship between allergic rhinitis and LPR presence (Alharethy et al, 2018), while another identified that GORD is significantly associated with the presence of post-nasal drip (Morimoto et al, 2021). Liu et al (2023) noted that the effects of LPR on quality of life are complicated by poor discrimination between LPR and GORD.…”
Section: Consequences and Associated Conditionsmentioning
confidence: 99%